Determination of reservoir drainage area for constant pressure systems using well test data - Escobar, Freddy Humberto; Hernández, Yuly Andrea; Tiab, Djebbar (CT&F - Ciencia, Tecnología y Futuro, 2010)
In this work, the conventional cartesian straight-line pseudosteady-state solution and the Total Dissolved Solids (TDS) solution to estimate reservoir drainage area is applied to constant-pressure reservoirs to observe its accuracy. It was found that it performs very poorly in such systems, especially in those having rectangular shape. On the other hand, the pseudosteady-state solution of the TDS technique performs better in constant-pressure systems and may be applied only to regular square- or circular-shaped reservoirs with a resulting small deviation error. Therefore, new solutions for steady-state systems in circular, square and rectangular reservoir geometries having one or two constant-pressure boundaries are developed, compared and successfully verified with synthetic and real field cases. Automatic matching performed by commercial software sometimes are so time consuming and tedious which leads to another reason to use the proposed equations.